The "Casting Couch" Scenario: Impact of Perceived Employment Benefit, Reporting Delay, Complainant Gender, and Participant Gender on Juror Decision-Making in Rape Cases - Mcintosh, Shona (Journal of interpersonal violence, 2022)
Recent legal and media reports of contemporary and historical rape and sexual assault cases have focused on the entertainment industry, particularly around the notion of the ?casting couch.? This scenario, in which a powerful figure obtains sometimes nonconsensual sexual acts from subordinate actors in exchange for employment, was used to explore the influence of rape myths and Sexual Economics Theory on mock-juror decision-making. Participant-jurors (n = 907) viewed video and written testimony of a complainant, accusing a male producer of rape. Complainant gender (male, female), delay before reporting the incident to the police (immediately, 6 months, 10 years), and complainant casting in the production were randomly varied (acting role secured, not secured). The strongest effects were that females (79.7%) were significantly more likely than males (62.7%) to deliver a guilty verdict and to recommend longer prison sentences for the offence. When the complainant did not secure the acting role, and they delayed reporting the incident for six months, there was an interaction between complainant gender and verdict. No interacting complainant gender effects on trial outcomes were found in the other delay conditions, or when the actor secured employment. Defendant guilt attributions to the male and female complainant were also differently influenced by rape myth belief levels and homophobic attitudes, but not beliefs in a just world. The casting couch euphemism, reported worldwide, suggests industry acceptance, and may sanitize the act of demanding sex and even committing rape. However, these results have important implications for any occupational setting in which men in positions of power may sexually exploit junior staff.